The drone warfare. Fact-checking, fake-pictures and necropolitics - Francisco López-Cantos (Cogent Social Sciences)
In this research, we deal with the use and effects for press news around images provided by unmanned aerial systems in conflict environments and, in particular, with the verification work that has been carried out to determine their validity, or in broad terms, their ‘objectivity’ and relationship with ‘reality’. To this end, we selected a sample of verification reports that detected and analyzed the dissemination of false images in the press recorded or related by drones in order to characterize the type of manipulation that has been carried out in the pictures and the procedures of detection used. We conclude that the use of this technology is becoming a perceived threat to public opinion because of its notoriety in the news, which currently focuses mainly on its use in military conflicts, overshadowing its usefulness for civilian and peaceful purposes.